Qisa char darwaish ka - Muhammad Yunus Hasrat (Ferozesons; Pakistan, 2012)
Qisa Char Darwaish Ka is a timeless tale of four mystics whose wisdom, humility, and adventures inspire lessons on selflessness and spiritual growth.